1993
DOI: 10.1152/ajpregu.1993.264.1.r73
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in CB57BL/6J mouse model of non-insulin-dependent diabetes mellitus

Abstract: The C57BL/6J (BL/6) mouse develops non-insulin-dependent diabetes mellitus (NIDDM) when fed a high fat-high simple carbohydrate (HFHSC) diet, whereas A/J mice do not. The purpose of the study was to determine whether hypertension occurred with NIDDM and whether it was sustained by sympathetic nervous system (SNS) hyperactivity. After 3 mo on an HFHSC diet with a low Na content (0.06%), awake, tail-cuff systolic blood pressure (BP) increased 20% above the control diet in BL/6 (138 +/- 3 vs. 115 +/- 4) but not i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
50
1
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 0 publications
6
50
1
3
Order By: Relevance
“…Our findings can possibly be interpreted as relevant for humans, as our study-used daidzein and equol concentrations that are within the range encountered in various populations that consume foods rich in isoflavones, and C57BL/6J mice have phenotype similar to that of human disease; the induction of obesity and insulin resistance under ad libitum access to a high-fat diet, and the maintenance of normal conditions under restriction to a low-fat chow diet, as in humans. [61][62][63] In addition, it will be the epoch-making discovery that daidzein affects ChREBP signaling, adiponectin and ghrelin as their relationships have yet to be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings can possibly be interpreted as relevant for humans, as our study-used daidzein and equol concentrations that are within the range encountered in various populations that consume foods rich in isoflavones, and C57BL/6J mice have phenotype similar to that of human disease; the induction of obesity and insulin resistance under ad libitum access to a high-fat diet, and the maintenance of normal conditions under restriction to a low-fat chow diet, as in humans. [61][62][63] In addition, it will be the epoch-making discovery that daidzein affects ChREBP signaling, adiponectin and ghrelin as their relationships have yet to be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the possible involvement of renal GSK3 in hypertension has not been examined. HF diet has been suggested to cause mild hypertension in C57/6J mice [18,20,21]. To determine if GSK3 plays a significant role in BP regulation in hyperinsulinaemic and insulin-resistant mice, we treated mice with GSK3 inhibitor peptide.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we explored the effect of GSK3 inhibition on glucose metabolism in an environmentally induced (high-fat [HF] diet) insulin-resistant obese mouse model of type 2 diabetes. Several studies have indicated that the C57BL/6J mouse strain on an HF diet is a suitable model for noninsulin-dependent diabetes mellitus and hypertension [18][19][20][21]. We chose this model because it closely mimics the common form of obesity and insulin resistance associated with human type 2 diabetes.…”
mentioning
confidence: 99%
“…Body weight, food and water ingestion were measured weekly throughout the study. This experimental model has been previously shown to induce obesity, type 2 diabetes mellitus and hypertension in C57BL/6 mice (Mills et al, 1993).…”
Section: Methodsmentioning
confidence: 97%